Osteoporosis dan Faktor Risikonya pada Lansia Etnis Jawa - Fatmah Fatmah (MEDIA MEDIKA INDONESIANA, 2008)
ABSTRACTOsteoporosis and its risk factors among Javanese elderly.Background: Osteoporosis is marked by the reduction of Bone Mass Density caused by multifactor. Osteoporosis is often found among elderly people, and at present still a problem in public health. At present data on prevalence of osteoporosis among Javanese elderly is not available. The objective of the study was to analyze the prevalence of osteoporosis among the elderly Javanese with its risk factors.Method: The risk of osteoporosis was measured by using Sahara Clinical Bone Sonometer, and T<-2.5 score was the criteria of osteoporosis.Result: The study showed that osteoporosis in the rural was lower than in the urban. Osteoporosis proportion among females was twice bigger than males. There was osteoporosis proportion development based on age group. Level of education, physical activity and occupational activity were related to osteoporosis. Respondents with low level of education had the mean and osteoporosis proportion higher than those with high/middle level of education. Percentage of osteoporosis among elderly with low level of physical and occupational activity was also higher than those who had high level. Calcium and protein intakes had no relevance withosteoporosis occurrence.Conclusions: Rural and urban areas, sex, age, level of education, work status, and weight are osteoporosis risk factors. Sex was the main osteoporosis determinant in this study. Keywords: Osteoporosis, sex, age, education, physical activity, occupational activity level ABSTRAKLatar belakang: Osteoporosis ditandai menurunnya densitas massa tulang yang disebabkan oleh multifaktor. Osteoporosis sering ditemukan pada lansia dan saat ini masih menjadi masalah kesehatan masyarakat. Saat ini informasi data epidemiologi tentang osteoporosis pada lansia etnis Jawa belum diketahui. Tujuan studi adalah untuk menganalisis proporsi dan faktor-faktor risiko osteoporosis lansia Suku Jawa.Metode: Studi cross sectional dilakukan masing-masing di 3 wilayah pedesaan dan perkotaan. Lokasi diperoleh melalui two stages stratified random sampling, sedangkan subyek melalui acak sederhana. Risiko osteoporosis dinilai dengan menggunakan alat Sahara Clinical Bone Sonometer dengan kriteria osteoporosis memiliki nilai skor T<-2,5.Hasil: Diperoleh 812 subyek penelitian. Proporsi osteoporosis di desa sedikit lebih rendah daripada kota. Perempuan memiliki proporsi osteoporosis dua kali lebih besar daripada laki-laki. Terdapat peningkatan osteoporosis berdasarkan umur. Tingkat pendidikan, beban pekerjaan harian, dan aktivitas fisik berhubungan dengan osteoporosis. Responden dengan tingkat pendidikan akhir yang rendah memiliki mean dan proporsi osteoporosis lebih tinggi daripada tingkat pendidikan tinggi/menengah. Persentase osteoporosis responden pada aktivitas fisik rendah dan beban pekerjaan harian rendah lebih tinggi dibandingkan tingkat berat. Asupan kalsium dan protein tidak berhubungan dengan kejadian osteoporosis.Simpulan: Wilayah tinggal, jenis kelamin, umur, tingkat pendidikan akhir, tingkat aktivitas fisik, dan tingkat beban pekerjaan harian merupakan faktor-faktor risiko osteoporosis lansia Etnis Jawa. Jenis kelamin adalah determinan utama osteoporosis dalam studi ini.